Glasgow Coma Scale (GCS) Sebagai Prediktor Kematian dan Kualitas Hidup Pasien Cedera Otak Traumatik di RSUP Dr. Sardjito - Taneo, Desy Chery Marlyn; Sudadi; Wisudarti, Calcarina Fitriani Retno (Jurnal Komplikasi Anestesi, 2021)
Background: Glasgow Coma Scale (GCS) as one of the most important predictors and a key measure in neurological assessment after brain injury. Apart from mortality, GCS is also a predictor of quality of life that can be measured using the Extended Glasgow Outcome Scale (GOSE). GOSE is a global assessment of independent living and social reintegration that is widely used as an outcome measure in brain injury research, to analyze long-term functional outcomes. Methods: This study used a retrospective cohort observational study design that aimed to predict mortality and quality of life using the Glasgow Coma Scale. This research has been conducted at the Medical Record Installation of Dr. Sardjito Hospital Yogyakarta using data from patients whom are treated with a diagnosis of traumatic brain injury at Dr. Sardjito Hospital from January 1, 2020 to December 31, 2020 retrospectively. Quality of life was calculated using the GOSE interview questionnaire. The relationship of GCS variables to mortality and quality of life was tested by the unpaired correlative hypothesis test followed by multivariate analysis with logistic regression methods. Results: There were 174 research subjects with a mean age of 37.51 (± 14.17) years, 124 male (71,3%) and 50 female (28.7%). Subjects GCS score < 8 had a higher risk of death than those with GCS score 13-15 (p<0.001, RR=18.3). Subjects with GCS score 9-12 had a higher risk of death than those with GCS score 13-15 (p<0.001, RR=9.71). Subjects with GCS score < 8 had a higher risk of unfavourable outcome than those with GCS score 13-15 (p<0.001, RR=9.49). Subjects with GCS score 9-12 had a higher risk of unfavourable outcome than those with GCS score 13-15 (p=0.001, RR=4.93). Conclusion: GCS on admission can be a predictor of mortality and quality of life for traumatic brain injury patients